2015
DOI: 10.1007/s11060-014-1701-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of glioblastoma with faint MGMT methylation-specific PCR product

Abstract: Methylation-specific polymerase chain reaction (MSP) for the promoter methylation status of O(6)-methylguanine-DNA-methyltranferase (MGMT) gene theoretically provides a positive or negative result. However, the faint MSP product is difficult to interpret. The aim of this study was to evaluate the significance of faint MSP product in glioblastoma (GBM). Critical concentrations of methylated control DNA, i.e., 100, 1, 0.5 and 0 % were run parallel with 116 newly diagnosed GBMs in order to standardize the interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Using pyrosequencing, Dunn and colleagues found a survival advantage of highly methylated tumors in a cohort of 109 patients homogeneously treated with temozolomide and standard radiotherapy (1). Similarly, another study reported an intermediate overall survival for patients with tumors producing a faint band in methylation-specific PCR compared with both unmethylated and distinctly methylated cases (32). Our analysis of TCGA data suggests that tumor purity is a predictor of survival, raising the question of which biological mechanism is responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 51%
“…Using pyrosequencing, Dunn and colleagues found a survival advantage of highly methylated tumors in a cohort of 109 patients homogeneously treated with temozolomide and standard radiotherapy (1). Similarly, another study reported an intermediate overall survival for patients with tumors producing a faint band in methylation-specific PCR compared with both unmethylated and distinctly methylated cases (32). Our analysis of TCGA data suggests that tumor purity is a predictor of survival, raising the question of which biological mechanism is responsible for this phenomenon.…”
Section: Discussionmentioning
confidence: 51%
“…A major disadvantage with using MSP and qMSP is that both these techniques only detect fully methylated MGMT promoter at the annealing sites of primers and probe (see Figure 1). This may lead to a problem in sensitivity; however, both these methods have in previous studies been found to be of prognostic value (1,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)39).…”
Section: Discussionmentioning
confidence: 99%
“…MGMT promoter methylation, regardless of whether measured by MSP, qMSP, PSQ, MS-HRM, MS-MLPA, or MethyLight qMSP, has been demonstrated to predict clinical outcome (1,13,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). PSQ has been claimed to be best technique to identify patients with GBM likely to benefit from therapy with temozolomide (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Cox regression model was used to adjust the influence of age, gender, KPS, extent of resection, bevacizumab treatment, isocitrate dehydrogenase 1 (IDH1) mutation and O 6 -methylguanine-DNA-methyltranferase (MGMT) status. The data of the MGMT status were from our previous study [2] and samples with methylation-specific PCR products of any intensity were regarded as a positive result. P -values were derived from two-tailed tests and p < 0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%
“…Patients’ survival has significantly improved since the use of radiotherapy with concomitant and adjuvant temozolomide (TMZ) chemotherapy and its median survival is 20.0 months at our institute [1, 2]. However, in comparing with other common malignancies in Taiwan, such as colon and breast cancers, its survival is still poor.…”
Section: Introductionmentioning
confidence: 99%